Character Based Leadership - Rifdan Rifdan; Kamardy Anugrah; Risma Niswaty; Sitti Hardiyanti Arhas (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
The leader has his own unique and distinctive nature, habits, temperament, character and personality so that it is his behavior and style that distinguishes him from others. This style will definitely color the behavior as well as the type of leadership. Leadership is aspirational power, creative spirit, and moral strength, which is able to influence members to change attitudes, so that they are in line with the wishes and aspirations of the leader. Leaders should be figures who become role models for those they lead. Some types of leadership in general are autocratic, charismatic, laisser faire, democratic, to make quality improvements. But if every time and in every case you have to give orders or directions, it will cause difficulties, because every time to do a good job it must be with the orders of the leadership, and if there is no order from the leadership not to do a good job, then continuous improvement of the quality of performance will be difficult to realize. A leader motivates followers through a leadership style based on Indonesian Local Wisdom, namely a character-based leadership style in realizing this, currently a leadership management style that integrates 18 character building values into the leadership style of University management is achieved so that the vision and mission of the university is achieved.